The Essence of Education - Sriatun, Sriatun; Sugiono, Sugiono; Kurniasih, Nanda Bella; Hendrizal, Hendrizal (Education Achievement: Journal of Science and Research, 2024)
Education is a complex and integral process in the formation of individuals and society. This research aims to explore the nature of education as a phenomenon that goes beyond the mere transfer of knowledge and skills, but also involves aspects such as character formation, development of critical abilities, and preparation for life in society. Through a comprehensive literature review, this research investigates various perspectives and concepts about the nature of education that have been proposed by leading educational experts and thinkers. The results of the analysis highlight the importance of education as a tool to facilitate the holistic growth of individuals, promote social inclusion, and build the foundation for sustainable development. These findings make an important contribution to our understanding of the important role of education in shaping a better future for society as a whole.